Advances in Transcatheter Electrosurgery for Treating Valvular Heart Disease. (2021) - Khan, affar M; BCh, BM; PhD, PhD; Lisko, John C; MD, MD; Yildirim, Dursun Korel; MS, MS; Rogers, Toby; BCh, BM; PhD, PhD; ,; Ratnayaka, Kanishka; et al.
No abstract available